PENGARUH COMPANY CHARACTERISTICS DAN RISK MANAGEMENT COMMITTEE TERHADAP ENTERPRISE RISK MANAGEMENT DIMENSI ISO 31000:2009 - IRMA TRIYANTI, DINI (Jurnal Akuntansi AKUNESA, 2018)
The objective of this research is the influance of company characteristics consisting of leverage, financial reporting risk, complexity, firm industry, size and risk management committee on enterprise risk management disclosure based on ISO 31000:2009. This study uses purposive sampling as a sampling technieque so it obtanied 353 companies by 3 study years so the total datas are 1.059 non financial listed companies on Indonesia Stock Exchange according to the criterias. By using Partial Least Square (PLS), the result shows that size and risk management committee have relation with enterprise risk management, but leverage, financial reporting risk, complexity, and firm industry has no relation with enterprise risk management. This shows that extreme leverage, high financial reporting risk, high bussiness complexity, and high profile industry companies are not able to encourage companies to conduct enterprise risk management disclosures.Keyword: Company Characteristics, Risk Management Committee, EnterpriseRisk Management, ISO 31000:2009